2018
DOI: 10.1002/epi4.12249
|View full text |Cite
|
Sign up to set email alerts
|

Post‐stroke seizure—Do the locations, types and managements of stroke matter?

Abstract: SummaryObjectiveTo determine the incidence of post‐stroke seizures and the associated risk factors in a government‐restructured hospital in Singapore.MethodsThis retrospective study included consecutive patients (age ≥21 years) admitted to the stroke rehabilitation facility at Changi General Hospital, Singapore, between June 2008 and May 2017, with a minimum post‐discharge follow‐up of 6 months. Patients with known epilepsy central nervous system infection or tumor, a history of neurosurgery and or missing dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
10
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 36 publications
4
10
1
1
Order By: Relevance
“…Approximately 9.8% of patients with cortical lesions had post-stroke seizures compared to 3.8% risk in subcortical lesions in one study [22]. Strokes in anterior vascular territories are more likely to cause seizures compared to posterior ones attributed to the fact that the anterior vascular territory involves larger areas of the cortex [24]. In addition, there appears to be an association with increased risk for development of stroke related epilepsy if the temporal lobes are affected [25][3].…”
Section: Pathomechanism Of Seizures After Ischemic and Hemorrhage Strmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 9.8% of patients with cortical lesions had post-stroke seizures compared to 3.8% risk in subcortical lesions in one study [22]. Strokes in anterior vascular territories are more likely to cause seizures compared to posterior ones attributed to the fact that the anterior vascular territory involves larger areas of the cortex [24]. In addition, there appears to be an association with increased risk for development of stroke related epilepsy if the temporal lobes are affected [25][3].…”
Section: Pathomechanism Of Seizures After Ischemic and Hemorrhage Strmentioning
confidence: 99%
“…The incidence of seizures following strokes varies greatly from 2% to 20% [6][7][8][24][29] and overall seem to have a higher incidence following hemorrhage stroke [30] and following SAH [31] (Table 2.). One of the largest prospective multicenter studies showed the overall incidence of seizures to be about 10.6% following ICH and about 8.6% following ischemic strokes [16].…”
Section: Incidence Of Post-stroke Seizuresmentioning
confidence: 99%
“…[59] The antiepileptic mechanisms of VPN are through blockade of presynaptic Na-channel-mediated glutamate release, inhibition of TNF-α and IL-1 β which play a role in the augmentation of presynaptic Ca and Na permeability. [60,61] The site of stroke lesions has been reported as a chief clinical factor enduring tendency to generate further and additional seizures. Several studies have established that early PSS is an independent risk factor for the development of late and repeated seizures.…”
Section: Vinpocetine and Postischemic Stroke Immunological And Inflammentioning
confidence: 99%
“…Tilstanden er hyppigere hos eldre pasienter og defineres som to eller flere tilbakevendende anfall mer enn fire uker e er gjennomgå hjerneslag (7). Infarktets størrelse ser ut til å vaere en risikofaktor (6, 7), noe som kan forklare at hjerneslag i fremre del av hjernens kretsløp i større grad ser ut til å føre til epilepsi enn hjerneslag i bakre kretsløp, fordi det involverer større deler av hjernen (8). Det ser også ut til at affeksjon av temporallappene øker risikoen for utvikling av senere epilepsi (9).…”
Section: Da Pasienten Kom Til Ny Kontroll Ved Nevrologisk Poliklinikk Noen Måneder Senere Fortalte Hun Om Et Nytt Anfall Igjen Skjedde Deunclassified